Topological LC-circuits based on microstrips and observation of electromagnetic modes with orbital angular momentum - Li, Yuan; Sun, Yong; Zhu, Weiwei; Guo, Zhiwei; Jiang, Jun; Kariyado, Toshikaze; Chen, Hong; Hu, Xiao (Nature communications, 2018)
New structures with richer electromagnetic properties are in high demand for developing novel microwave and optic devices aimed at realizing fast light-based information transfer and information processing. Here we show theoretically that a topological photonic state exists in a hexagonal LC circuit with short-range textures in the inductance, which is induced by a band inversion between p - and d -like electromagnetic modes carrying orbital angular momentum, and realize this state experimentally in planar microstrip arrays. Measuring both amplitude and phase of the out-of-plane electric field accurately using microwave near-field techniques, we demonstrate directly that topological interfacial electromagnetic waves launched by a linearly polarized dipole source propagate in opposite directions according to the sign of the orbital angular momentum. The open planar structure adopted in the present approach leaves much room for including other elements useful for advanced information processing, such as electric/mechanical resonators, superconducting Josephson junctions and SQUIDs. Both photonic topological structures and optical angular momentum have been investigated over the last few years. Here, the authors propose and demonstrate that a honeycomb LC circuit can support topological photonic states with band inversion between modes that carry orbital angular momentum.